1978
DOI: 10.1159/000214241
|View full text |Cite
|
Sign up to set email alerts
|

New Chromogenic Peptide Substrates for Factor X<sub>a</sub>

Abstract: The factor-Xa-sensitive substrate Bz-Ile-Glu-Gly-Arg-p-nitroanilide has been made more sensitive by making ester and amide derivatives of the γ-carboxyl group of the glutamyl residue. The morpholinyl and piperidyl amides react 2.5 times more rapidly with factor Xa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1980
1980
1997
1997

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…The structure of synthetic substrates and their efficiency for various blood derived serine proteases such as plasmin, factor Xa, thrombin, kallikreins and urokinase, factors VIIa, IXa, XIa, and XIIa, and activated protein C were analyzed in several previous publications (Sherry et al, 1966;Morita et al, 1977;Aurell et al, 1978;Claeson et al, 1978; Lonsdale -Eccles et al, 1980;McRae et al, 1981;Lottenberg et al, 1983Lottenberg et al, , 1986Castillo et al, 1983;Cho et al, 1984;Harnois-Pontoni et al, 1991;Butenas et al, 1992Butenas et al, , 1993Butenas et al, , 1995. The data concerning the influence of the substrate P n -P 1 -P n ′ structure on its efficiency for a given enzyme are controversial (Morita et al, 1977;McRae et al, 1981;Lottenberg et al, 1983;Cho et al, 1984) and do not provide clear answers about the most favorable amino acids at the various P positions (Harnois-Pontoni et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…The structure of synthetic substrates and their efficiency for various blood derived serine proteases such as plasmin, factor Xa, thrombin, kallikreins and urokinase, factors VIIa, IXa, XIa, and XIIa, and activated protein C were analyzed in several previous publications (Sherry et al, 1966;Morita et al, 1977;Aurell et al, 1978;Claeson et al, 1978; Lonsdale -Eccles et al, 1980;McRae et al, 1981;Lottenberg et al, 1983Lottenberg et al, , 1986Castillo et al, 1983;Cho et al, 1984;Harnois-Pontoni et al, 1991;Butenas et al, 1992Butenas et al, , 1993Butenas et al, , 1995. The data concerning the influence of the substrate P n -P 1 -P n ′ structure on its efficiency for a given enzyme are controversial (Morita et al, 1977;McRae et al, 1981;Lottenberg et al, 1983;Cho et al, 1984) and do not provide clear answers about the most favorable amino acids at the various P positions (Harnois-Pontoni et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…With our series of substrates, the effect seems to be totally in kat. Factor Xa has been widely studied with synthetic substrates (Iwanaga et al, 1978;Lottenberg et al, 1981;Lonsdale-Eccles et al, 1980;Svendsen et al, 1972), and some subsite mapping has been carried out at P3 (Aurell et al, 1976(Aurell et al, , 1977(Aurell et al, ,1978. Many of these studies reported only relative reactivities without kinetic constants and did not examine a wide variety of P3 amino acid residues.…”
Section: Discussionmentioning
confidence: 99%